2016
DOI: 10.1128/jb.00913-15
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Contributions of Enzymic Functional Groups to the 2′,3′-Cyclic Phosphodiesterase, 3′-Phosphate Guanylylation, and 3′-ppG/5′-OH Ligation Steps of the Escherichia coli RtcB Nucleic Acid Splicing Pathway

Abstract: Escherichia coli RtcB is a founding member of a family of manganese-dependent RNA repair enzymes that join RNA 2=,3=-cyclic phosphate (RNA>p) or RNA 3=-phosphate (RNAp) ends to 5=-OH RNA ( HO RNA) ends in a multistep pathway whereby RtcB (i) hydrolyzes RNA>p to RNAp, (ii) transfers GMP from GTP to RNAp to form to RNAppG, and (iii) directs the attack of 5=-OH on RNAppG to form a 3=-5= phosphodiester splice junction. The crystal structure of the homologous archaeal RtcB enzyme revealed an active site with two cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 14 publications
2
23
0
Order By: Relevance
“…We found that RtcB-mediated ligations were more efficient than ligations performed by endogenous ligases in HeLa cells. We also confirmed that the multistep RtcB mechanism proceeded via a terminal monophosphate intermediate [29][30][31][32]35,36]. This implies that 3 0 -phosphorylated miRNAs might also function as probes for the new CLIP method using RtcB.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…We found that RtcB-mediated ligations were more efficient than ligations performed by endogenous ligases in HeLa cells. We also confirmed that the multistep RtcB mechanism proceeded via a terminal monophosphate intermediate [29][30][31][32]35,36]. This implies that 3 0 -phosphorylated miRNAs might also function as probes for the new CLIP method using RtcB.…”
Section: Discussionsupporting
confidence: 74%
“…5B,C). Together with the appearance of a signal (peak#2) corresponding to the respective 3′‐phosphate intermediate, these data provide further evidence for the multistep pathway that proceeds with hydrolysis of the cyclic phosphate followed by ligation of the 3′‐phosphate intermediate [29–32,35,36]. The data were confirmed in a second experiment in which the excess Mn 2+ was not depleted prior to LC‐MS analysis (data not shown).…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations